Islamic Religious Education Teachers' Strategies in Instilling Environmental Awareness Character - Hadi Saputra Panggabean; Afriadi Sanusi; Nanda Rizky (Sekolah Tinggi Agama Islam Sumatera Medan, 2026)
This study aims to analyze the strategies employed by Islamic Religious Education teachers to internalize character education values in fostering students' environmental care attitudes at SMA Negeri 1 Medan, SMA Negeri 2 Medan, and SMA Negeri 3 Medan. The study adopted a qualitative approach with a descriptive research design. Data were collected through interviews, participant observation, and document analysis involving six Islamic Religious Education teachers and 60 students. The data were analyzed using the interactive model proposed by Miles, Huberman, and Saldaña. The findings reveal that the internalization of environmental care character values was implemented through three main strategies: integrating environmental values into Islamic Religious Education learning materials, implementing environment-based project learning, and reinforcing values through religious activities and reflective practices. These strategies facilitated an internalization process that connected religious understanding with authentic experiences, habitual practices, and the school's religious culture, enabling students to perceive environmental stewardship as an integral part of amanah (trust) and Islamic moral conduct (akhlaq). This study contributes to Islamic Religious Education scholarship by demonstrating that fostering environmental care character requires the integration of contextual learning, experiential activities, spiritual guidance, and a supportive school culture.